Genomic and biological aspects of resistance to selective poly(ADP‐ribose) glycohydrolase inhibitor PDD00017273 in human colorectal cancer cells. Issue 2 (26th August 2022) - Tsuda, Kaede; Kurasaka, Chinatsu; Ogino, Yoko; Sato, Akira
Abstract: Background: Poly(ADP‐ribose) glycohydrolase (PARG) is a key enzyme in poly(ADP‐ribose) (PAR) metabolism and a potential anticancer target. Many drug candidates have been developed to inhibit its enzymatic activity. Additionally, PDD00017273 is an effective and selective inhibitor of PARG at the first cellular level. Aims: Using human colorectal cancer (CRC) HCT116 cells, we investigated the molecular mechanisms and tumor biological aspects of the resistance to PDD00017273. Methods and results: HCT116R PDD, a variant of the human CRC cell line HCT116, exhibits resistance to the PARG inhibitor PDD00017273. HCT116R PDD cells contained specific mutations of PARG and PARP1, namely, PARG mutation Glu352Gln and PARP1 mutation Lys134Asn, as revealed by exome sequencing. Notably, the levels of PARG protein were comparable between HCT116R PDD and HCT116. In contrast, the PARP1 protein levels in HCT116R PDD were significantly lower than those in HCT116. Consequently, the levels of intracellular poly(ADP‐ribosyl)ation were elevated in HCT116R PDD compared to HCT116. Interestingly, HCT116R PDD cells did not exhibit cross‐resistance to COH34, an additional PARG inhibitor. Conclusion: Our findings suggest that the mutated PARG acquires PDD00017273 resistance due to structural modifications. In addition, our findings indicate that PDD00017273 resistance induces mutation and PARP downregulation. These discoveries collectively provide a better understanding of the anticancer candidate PARG inhibitors in terms of resistance mechanisms and anticancer strategies.